Artificial Ground Water Recharge By Innovative Method - R. Shikhare, Rohit; R. Patil, Ashwini (Journal of Neonatal Surgery, 2025)
Artificial groundwater recharge is an effective solution to address the growing water scarcity and depletion of groundwater resources caused by excessive extraction and urbanization. Traditional recharge methods, such as percolation pits, trenches, and rainwater harvesting systems, are widely used but often achieve only 60–70% efficiency, which is insufficient to meet increasing water demand. This study explores innovative methods for enhancing groundwater recharge, focusing on indoor and outdoor techniques that maximize percolation and optimize water usage. The indoor method involves the installation of an Excess Water Line (EWL) in residential buildings to divert unfiltered water from water purifier directly into borewells through connectivity of Excess water line. The outdoor method utilizes funnel-shaped or trapezoidal structures with deep perforated pipes to infiltrate rainwater, river overflow, and runoff into the ground, with sensors and water meters monitoring discharge and groundwater levels. A case study of a residential society with 164 tenements demonstrates that EWL implementation can save over 1.1 million liters of water annually, with potential savings scaling to several thousand million liters in urban areas. These innovative approaches not only replenish aquifers efficiently but also reduce dependence on municipal water supply, prevent land subsidence, and support sustainable water management for future generations